Ichthyofaunal diversity of Bhagairia Lake in Bardiya District, Nepal - Bista, Abhishekh; Mandal, Ram Bhajan; Yadav, Choudhary Nagendra Roy; Rayamajhi, Asha; Gurung, Gun Bahadur (Nepalese Journal of Zoology, 2022)
This study was conducted to assess the ichthyofaunal diversity of Bhagairia Lake located in Bardiya district, Nepal from August 2019 to February 2020. For this research monthly sampling was done to assess ichthyofaunal diversity and water quality parameters i.e. water temperature, water transparency, total dissolved solids, dissolved oxygen, pH, alkalinity, total hardness, ammonia, phosphate and nitrate from six sites around the lake. A total number of 30 species of fish belonging to 8 orders, 13 families and 23 genera were recorded. Among these, Cypriniformes and Cyprinidae were the dominant order and family covering 50% and 44 % of fish species, respectively. Puntius sophore was found to be the dominant fish species with a catch composition of 12%. Maximum fish catch (214 individuals) was recorded in February whereas, minimum fish catch (140 individuals) was recorded in August. The fish catch was found to be positively correlated with dissolved oxygen (r= 0.912), pH (r= 0.876), alkalinity (r= 0.840) and total hardness (r= 0.876). Shannon diversity index was the highest in August (3.14) and lowest in November (2.87). Margalef's richness index was highest in the month of August (5.276) and lowest in February (3.727) whereas, Sheldon evenness index was highest in February (0.925) and lowest in September (0.823). This study revealed that Bhagairia Lake is rich in fish faunal diversity and consists of native, cultivable, ornamental and rare species of fish.